Antibodies against Actinobacillus pleuropneumoniae, Mycoplasma hyopneumoniae and influenza virus and their relationships with risk factors, clinical signs and lung lesions in pig farms with one-site production systems in Brazil - Baraldi, T. G. [UNESP]; Cruz, N. R.N. [UNESP]; Pereira, D. A. [UNESP]; Galdeano, J. V.B. [UNESP]; Gatto, I. R.H. [UNESP]; Silva, A. F.D.; Panzardi, A.; Linhares, D. C.L.; Mathias, L. A. [UNESP]; de Oliveira, L. G. [UNESP] (Elsevier, 2019)
A study was conducted on 21 pig herds using one-site production system in the southeast region of Brazil to assess the relationships among serological results for primary pathogens involved in respiratory diseases (Actinobacillus pleuropneumoniae, App; Mycoplasma hyopneumoniae, Mhyo; and swine influenza virus, SIV), cough index, pneumonia index, pleuritis and herd characteristics. The prevalence of antibodies against Mhyo and SIV increased throughout the raising phases, with the highest prevalence in slaughtered pigs (> 40%), while pigs in 65% (14/21) of nurseries demonstrated marked seroprevalence of App that decreased until the day of slaughter. Pleuritis and pulmonary consolidations were recorded in 9.0 and 72.4%, respectively, of the 908 evaluated lungs. Histopathological analysis of the lung lesions revealed suppurative bronchopneumonia in almost half of the lungs (48.9%). Regression analyses were conducted to identify risk factors associated with the cough index; pleuritis; pulmonary consolidation; and App, Mhyo and SIV serological results. All-in-all-out management in nursery buildings reduced the seroprevalence of Mhyo in herds. App seroprevalence was associated with pleuritis, and the presence of cough episodes in growing pigs was associated with SIV seropositivity in nursery pigs.
Keywords: ELISA; Enzootic pneumonia; Pleuritis; Porcine respiratory disease complex; Risk factors